'Safe Ships and Clean Seas': Evading a mandatory shipping code for Antarctic waters - Julia Jabour (2009)
Shipping is an inherently dangerous activity, with heightened risks in polar waters owing to inadequate charts, extreme weather and the presence of icebergs and sea ice, among other factors. In this context, there are currently two proposals before the Internatio nal Maritime Organization (IMO) designed to addtess and mitigate these risks: first, the adoption of voluntary guidelines for ships operating in polar waters;I second the development of a mandatory polar shipping code.' These initiatives respond to the recent grounding of vessels within the Antarctic Peninsula region and the sinking of the MS Exp lore r south of King George Island in November 2007.3 l Understandably, stakeholders are concerned about the future management and regulatory options which are under consideration given the existing problems of operating within the Antarctic region. These existing challenges are likely to be exacerbated by climate change, which is predicted to affect the formation, composition, extent and duration ofAntarctic sea ice.'